Pengaruh PDRB IPM Jumlah Penduduk dan UMK Terhadap Tingkat Penganggguran Terbuka di Jawa Tengah - H, Hasim; A’yun, Indanazulfa Qurrota (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the effect of PDRB, HDI, Population and UMK on the Open Unemployment Rate in Central Java 2018-2022. This study uses secondary data with a quantitative approach. The analysis tool used is STATA 14. The type of data used in this study is panel data consisting of 35 districts/cities in Central Java Province in the 2018-2022 period. The research data comes from the official website of the Central Java Provincial Statistics Agency. The results of the study obtained indicate that PDRB, Population and UMK have a positive effect on the Open Unemployment Rate in Central Java, while HDI has a negative effect on the Open Unemployment Rate in Central Java.